2001
DOI: 10.2135/cropsci2001.412493x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Response to Water: A QTL Analysis of Drought Tolerance

Abstract: Soybean [Glycine max (L.) Merr.] yield, when regressed on water needed to replenish 0 to 100% seasonal evapotranspiration (ET), generates an estimate of season‐specific water‐use efficiency (WUE). The impact of unpredictable water deficits might be lessened if high‐yielding genotypes had a smaller beta. Our objective was to determine the genetic basis of beta and carbon isotope discrimination (CID), a theorized indicator of transpiration efficiency (TE). A ‘Minsoy’ × ‘Noir 1’ population of 236 recombinant inbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
223
2
29

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 448 publications
(284 citation statements)
references
References 45 publications
30
223
2
29
Order By: Relevance
“…The different concentrations of seed constituents among years in both locations reflected the effect of environmental factors on seed composition constituents. It was reported that seed constituents were affected by environment [16,17,40], temperature [17,18], drought [19,21,22,40], and nutrients in soil and seed [3][4][5]. It was reported that seed constituents vary in the same soybean cultivar grown in different years or under different environments in the same year [26].…”
Section: Seed Yield Protein Oil and Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different concentrations of seed constituents among years in both locations reflected the effect of environmental factors on seed composition constituents. It was reported that seed constituents were affected by environment [16,17,40], temperature [17,18], drought [19,21,22,40], and nutrients in soil and seed [3][4][5]. It was reported that seed constituents vary in the same soybean cultivar grown in different years or under different environments in the same year [26].…”
Section: Seed Yield Protein Oil and Fatty Acidsmentioning
confidence: 99%
“…However, seed composition have also shown to be affected by environment [16,17], genotype, maturity, diseases [18][19][20], temperature [17,18] and drought [19,21,22], nutrients in soil and seed [23][24][25], and planting date [26,27]. For example, it was reported that [26] seed composition varied in the same cultivar grown in different years or under different environments in the same year, and seed protein concentration increased as planting was delayed.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors (Mansur et al, 1996;Brummer et al, 1997;Specht et al, 2001) have reported other quantitative loci with different magnitudes, locations, and genetic populations.…”
Section: Discussionmentioning
confidence: 99%
“…Rodrigues et al (2010). Os utilizados para seleção quanto à proteína foram relatados por Orf et al (1999), Sebolt et al (2000), Csanádi et al (2001), Specht et al (2001), Chapman et al (2003), Chung et al (2003), Tajuddin et al (2003), Hyten et al (2004), Reinprecht et al (2006), Chen et al (2007) e Soares et al (2008).…”
Section: Methodsunclassified
“…Vários marcadores de locos de caracteres quantitativos (QTL) foram relatados para teores de óleo e proteína em soja (Sebolt et al, 2000;Csanádi et al, 2001;Specht et al, 2001;Chung et al, 2003;Chapman et al, 2003;Tajuddin et al, 2003;Fasoula et al, 2004;Hyten et al, 2004;Zhang et al, 2004;Panthee et al, Pesq. agropec.…”
Section: Introductionunclassified